IMPLEMENTASI METODE AN-NASHR DALAM PEMBELAJARAN PAI KELAS VI SD NEGERI 1 ULIM KABUPATEN PIDIE JAYA - Nanda Insyirah; Mislinawati; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students' memorization ability, particularly at the elementary school level, is greatly influenced by the memorization method used. Based on preliminary observations, students experience difficulties in memorizing short surahs, such as lack of fluency in pronouncing the verses and inaccuracies in recitation according to the rules of tajwid. Therefore, learning to memorize the Qur’an at the elementary school level requires appropriate methods so that students are not only able to memorize but also understand the recitation properly. The An-Nashr method is one of the methods that emphasizes gradual, structured learning accompanied by repetition, which is expected to strengthen students’ memorization. This study aims to describe the implementation of the An-Nashr method in Islamic Religious Education learning on the topic of reciting Surah Al-A’la with the sub-theme of memorizing Surah Al-A’la. This study employed a qualitative approach with a descriptive design. The research subjects consisted of 20 students who participated in the learning process. Data were collected through observation and performance tests. The results of the study indicate that the implementation of the An-Nashr method is carried out through gradual repetition. The repetition process was proven to improve students’ fluency, accuracy of recitation, and memory of the surah being memorized. Therefore, the An-Nashr method can be considered an effective alternative in improving the ability of elementary school students to memorize surahs.